2004
DOI: 10.1002/ejsp.235
|View full text |Cite
|
Sign up to set email alerts
|

Values, identities and social constructions of the European Union among Turkish university youth

Abstract: The present study aimed to investigate Turkish university youth's constructions concerning the European Union (EU) and their reactions to the EU's December 2002 Copenhagen summit decision to delay discussion of Turkey's entry to the EU. Specifically it aimed to show that socio-political identities among Turkish youth were related to historical developments in Turkey's past and that these identities had associations with values of ethnocentricism, patriotism, and secularism. Furthermore it was predicted that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…In turn, social identification is increased by the charismatic leader's emphasis on followers' collective identities and shared values (e.g., Shamir, Zakay, Breinin & Popper, 1998). Furthermore, research highlights the link between values and social identities such that group members who share a common social identity also share common value orientations (e.g., Heaven, 1999;Hortaçsu & Cem-ersoy, 2005).…”
Section: An Alternate Perspective: Social Identity Framing For Socialmentioning
confidence: 99%
“…In turn, social identification is increased by the charismatic leader's emphasis on followers' collective identities and shared values (e.g., Shamir, Zakay, Breinin & Popper, 1998). Furthermore, research highlights the link between values and social identities such that group members who share a common social identity also share common value orientations (e.g., Heaven, 1999;Hortaçsu & Cem-ersoy, 2005).…”
Section: An Alternate Perspective: Social Identity Framing For Socialmentioning
confidence: 99%
“…SDO did not significantly correlated with any type of values in the present study. However, there were several indications that nationalism correlates with values in previous studies in Turkey (Hortaçsu & Cem-Ersoy, 2005;Kuşdil & Şimşek, 2007). As for the associations between Schwartz's values and other key variables, Gürşimşek and Göregenli (2005) reported that participants with higher scores on traditionality power and conformity were seen to have higher scores on system justification.…”
Section: Discussionmentioning
confidence: 92%
“…In this historical respect, cultural, regional and religious differences and occasionally conflict have characterized Turkish-European relations. Thus, the main dimensions of differentiation between Turkey and Europe are differences with respect to EU criteria concerning economy and human rights and cultural/religious differences reflected by the history of conflict (Hortaçsu & Cem-Ersoy, 2005;Kuşdil & Şimşek, 2007). The last two decades were characterised by political and social reforms in Turkey since accession negotiations started in October, 2005.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations